1993
DOI: 10.1089/aid.1993.9.475
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 Replication in H9 Cells by Nystatin-A Compared with Other Antiviral Agents

Abstract: Nystatin A was compared in vitro with amphotericin B, AZT, or foscarnet for their respective abilities to inhibit the replication of human immunodeficiency virus type 1 (HIV-1) in H9 cells. HIV-1-infected H9 cells were cultured for 7 days in the presence of each of these drugs, at various concentrations. Reverse transcriptase activity and p24 antigen production were quantitated. Untreated, HIV-1-infected H9 cells served as the control. Nystatin A inhibited viral replication most effectively at 10 micrograms/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…MS8209 may therefore be useful to define the early steps of HIV-1 entry and their viral and cellular requirements. Amphotericin B and its derivatives, as well as nystatin A, are structurally related to MS8209 and also exert an antiviral effect on HIV-1 (28,31). Although a detailed study of their mechanisms of action has not yet been reported, our preliminary experi-ments indicate a mode of action similar to that of MS8209.…”
Section: ;mentioning
confidence: 70%
“…MS8209 may therefore be useful to define the early steps of HIV-1 entry and their viral and cellular requirements. Amphotericin B and its derivatives, as well as nystatin A, are structurally related to MS8209 and also exert an antiviral effect on HIV-1 (28,31). Although a detailed study of their mechanisms of action has not yet been reported, our preliminary experi-ments indicate a mode of action similar to that of MS8209.…”
Section: ;mentioning
confidence: 70%
“…Nystatin is a cholesterol-binding antibiotic that selectively disrupts HIV-1 receptors residing on cholesterolcontaining platforms 25 and has been demonstrated to interfere with in vitro HIV-1 infectivity (IC 50 ϭ 4 M) in H9, HUT-78, and U937 cells, but has little effect in vivo except against candidiasis. 26 HLE and CXCR4 copatching stimulated by ␣ 1 PI was found to be completely abrogated by pretreating for 60 minutes with 50 M nystatin (data not shown).…”
Section: Hle Binding To the Hiv-1 Fusion Domainmentioning
confidence: 93%
“…Because virions bud from cholesterol-rich microdomains, cholesterol depletion results in a reduced amount of cholesterol on the viral membrane, which in turn inhibits viral infectivity. Cholesterol-chelating compounds like nystatin have also been reported to inhibit HIV-1 infectivity [42,47]. Recently, we have shown that the cholesterol-binding compound amphotericin B methyl ester (AME), a water-soluble derivative of amphotericin B, inhibits HIV-1 entry [48–51].…”
Section: Lipids In Retrovirus Replicationmentioning
confidence: 99%